Failure mechanism of MCrAlY coating at the coating‐substrate interface under type I hot corrosion. Issue 9 (26th March 2019) - Zhang, Pimin; Peng, Ru Lin; Li, Xin‐Hai
Abstract: MCrAlY coatings are widely used to provide protection of hot component in modern gas turbine engines against high‐temperature oxidation and hot corrosion. Coating‐substrate interface, where the substrate is only partially covered by the ﻿coatings, is vulnerable to the hot corrosion attack. The accelerated degradation at the coating‐substrate interface can cause fast spallation of the coating, leading to the early failure of the gas turbine components. In this paper, MCrAlY powder was deposited on IN792 disks by high‐velocity oxygen‐fuel spraying. The hot corrosion behavior of the coated sample was investigated using (0.8Na, 0.2K)2 SO4 salt deposition at 900°C in lab air. Results showed a minor attack in the coating center, however, an accelerated corrosion attack at the coating‐substrate interface. The fast growth of corrosion products from substrate caused large local volume expansions at the coating‐substrate interface, resulting in an early coating spallation. Abstract : Accelerated type I hot corrosion attack at the MCrAlY coating‐IN792 interface can cause premature coating spallation. During the corrosion reaction, fast growth of corrosion products from IN792 caused large local volume expansions at the coating‐substrate interface. The severe deformation cracked the coating by a stress‐assisted corrosion degradation mode.